2020
DOI: 10.1177/1059840520902511
|View full text |Cite
|
Sign up to set email alerts
|

A School Nurse–Led Asthma Intervention for School-Age Children: A Randomized Control Trial to Improve Self-Management

Abstract: Asthma is a common disease in children, and obtaining basic knowledge and skills to manage asthma symptoms is critically important. This study examined the effectiveness of a theoretically based school nurse–led asthma intervention on asthma symptoms, self-management, peak flow meter usage, daily activities, and school absences in children 7–12 years old. A randomized controlled, two-group, repeated measures design was conducted in eight public schools. Data collection occurred at three time points. The treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The purpose of this review was to identify the current evidence on the impact of school nurse-led asthma intervention programs. The school nurse’s role in the included studies varied between providing educational interventions for asthmatic children ( D. M. Carpenter et al, 2016 ; Isik et al, 2020 ; Persaud et al, 1996 ; Simoneau et al, 2020 ), supervising the administration of preventive asthma medication ( Harrington et al, 2018 ; Trivedi et al, 2018 ), and running a school asthma clinic ( Salisbury et al, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The purpose of this review was to identify the current evidence on the impact of school nurse-led asthma intervention programs. The school nurse’s role in the included studies varied between providing educational interventions for asthmatic children ( D. M. Carpenter et al, 2016 ; Isik et al, 2020 ; Persaud et al, 1996 ; Simoneau et al, 2020 ), supervising the administration of preventive asthma medication ( Harrington et al, 2018 ; Trivedi et al, 2018 ), and running a school asthma clinic ( Salisbury et al, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 25 to 490. The target population of the included studies was children alone (D. M. Carpenter et al, 2016;Harrington et al, 2018;Isik et al, 2020;Salisbury et al, 2002;Trivedi et al, 2018), children with their parents (Persaud et al, 1996), or children and school nurses (Simoneau et al, 2020). Notably, none of the studies included in this review indicated the qualification of the school nurses who led the interventions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations